Celtic theorems as an individual option in Portuguese Lusitania - Gaspar, Catarina (2018)
This paper illustrates how the individual choice works out in the building the communities' organic religion diversity. The religious behaviour of a roman signifier devoted to the roman goddess Victoria and to the indigenous goddess Trebaruna, shows both the flexibility within Egiditanian society and the personal religious behaviour of a well to do citizen.